Message from the Regional Director on World Health Day 2014 on Vector-borne diseases - Singh, Poonam Khetrapal (Indian Journal of Community Health, 2014)
Since time immemorial, humankind has co-habited with innumerable other living forms. Some of these have been responsible for transmitting diseases to human beings. Malaria, dengue, and kala-azar are just a few examples of such diseases of public health importance to us, that are grouped under the broad-term of vector-borne diseases. Vectors are small organisms, such as mosquitoes, bugs, ticks and freshwater snails,that can carry disease from person to person and from place to place.